Selection and probiotic characterization of exoenzyme-producing bacteria isolated from the gut of Catla catla (Actinopterygii: Cypriniformes: Cyprinidae) - D. Dutta; S. Banerjee; A. Mukherjee; K. Ghosh (Acta Ichthyologica et Piscatoria, 2015)
Background. Exoenzyme-producing gut microbiota and their likely use as probionts have been widely investigated in major carps. However, reports on exoenzyme-producing capacity together with inhibition of fish pathogens are scarce. The presently reported study aimed at characterization of novel probionts from the gastro-intestinal (GI) tract of an Indian major carp—catla, Catla catla (Hamilton, 1822) depending upon extracellular enzyme-production, antagonism against Aeromonas spp., growth in fish mucus, bile tolerance, and bio-safety to the target fish. Materials and methods. GI tracts were divided into proximal and distal parts, homogenized, and plated onto selective media plates following enrichment culture technique. Exoenzyme-producing isolates were selected through qualitative and quantitative assay of 6 enzymes. Inhibition of Aeromonas spp. was tested through ‘cross-streaking’ and ‘double-layer’ method. Tolerance to GI condition was determined by growth in sterilized fish mucus and exposure to bile juice. Bio-safety evaluation was done by intra-peritoneal injection of live candidate probiotics and co-culture with autochthonous gut bacteria. Further, 16S rDNA fragments from the putative probiotics were sequenced, edited, analysed, identified, and deposited to the GenBank. Results. Seventeen potent isolates were primarily selected through the ability of producing extracellular enzymes, viz., amylase, protease, lipase, cellulase, phytase, and xylanase. Further study portraying antagonism against Aeromonas salmonicida, A. hydrophila, and A. veronii led to select the strains CCH1A and CCH1Ph as putative probiotics. Both the strains were competent to grow in intestinal mucus and could resist diluted bile juice (9% and 10.5%, respectively). The isolates did not produce any disease symptom or mortality in Catla catla fingerlings during the 21 day trial and were competent to grow with other autochthonous isolates. On the basis of phenotypic characteristics and 16S rDNA sequence analysis, the strains CCH1A and CCHIPh were identified as Bacillus aerius (KF623288) and Bacillus sonorensis (KF623289), respectively. Conclusion. Exoenzyme-producing gut bacteria may inhibit the growth of pathogenic Aeromonas spp. and tolerate gastrointestinal condition. Further research is inevitable to explore their potentialities in aquaculture.